Produção da metilcelulose a partir da celulose do bagaço de cana-de-açúcar usando dois agentes metilantes: sulfato de dimetila e iodometano, para aplicação como aditivo na formulação de argamassas - Vieira, Júlia Graciele (2012)
In this work, methylcellulose (MC) was produced from sugarcane bagasse cellulose by heterogeneous route in alkaline medium, according to two methodologies: i) reaction with DMS, successive exchange of reagents and a step of mercerization and ii) reaction with iodomethane in two steps of mercerization. The synthesized methylcelluloses and a commercial methylcellulose sample, used as standard, have been evaluated as admixtures for adhesive mortars in civil construction by 2 methods, being added as a suspension in water (method 1) and in the powder form, dispersed in the mortar during its preparation (method 2). One of the main points of innovation of this study was to apply the polymers as a powder during mortar preparation, so that it approaches the commercial adhesive mortars, which consist of mixtures pre-dosed powder. In this study, methylcellulose produced using DMS (MCD), iodomethane (MCI) and commercial methylcellulose (MCC) were characterized according to their degree of substitution (DS) by chemical route, by Fourier Transform Infrared Spectroscopy (FTIR), X-Ray Diffraction (XRD), Differential Scanning Calorimetry (DSC), Thermogravimetric Analysis (TGA) and viscosity measurements. The modifications observed in the FTIR spectra showed the efficiency of methylation processes using DMS and iodomethane. The samples showed differences in water solubility, MCI was more soluble, and related to the crystallinity, the MCD presented more crystalline pattern and MCI more amorphous. The MCD was more thermally stable. The adhesion of mortars prepared by method 1 was close to the values obtained for reference mortar, particularly only to the MCD sample that increased by about 28% compared to reference. For the mortars produced by method 2, the direct addition of polymers effectively changed the properties of mortars, especially in relation to the adhesion, that increased by approximately 23% to mortar containing MCI, about 70% for MCD and 20% for MCC. It is observed that MCD samples perform best in all tests, this may be related to the higher DS for this sample, which favors the gel formation and the water retention, making the mortar more viscous and \"sticky\", altering the interactions between mortar and substrate and increasing the adhesion.